Penguatan Ketahanan Ekonomi Berbasis Potensi Lokal : Budidaya Jamur Tiram di Desa Gunung Hejo, Purwakarta - Eddy Junaedy; Eti Jumiati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The goal of this community service program is to increase the economic resilience of the Gunung Hejo Village community through the development of oyster mushroom cultivation, utilizing local potential sustainably. This activity is designed to reduce the community's dependence on traditional agriculture, which is vulnerable to market price fluctuations, climate uncertainty, and limited business diversification. Oyster mushroom cultivation was chosen as an alternative due to its broad market prospects, relatively simple production process, and the ability to produce high yields quickly.The method used in this program is participatory, educational, and applicable, with students and the community actively involved in every stage of the activity, from planning and outreach, technical training, to hands-on practice in making mushroom bags and maintaining oyster mushrooms. Intensive mentoring is provided to ensure the community not only understands the theory but also develops practical skills that can be applied independently. The results of this activity indicate that the community has successfully improved their understanding and technical skills related to oyster mushroom cultivation, including raw material selection, planting medium preparation, maintenance, and simple marketing strategies. Each baglog produced provides a sufficient yield for both household consumption and sale as a supplementary commodity, thus directly impacting local economic income. The implications of this program lie not only in the economic aspect but also in the development of an environmentally friendly and sustainable agricultural business model that can be replicated in other villages with similar potential. Furthermore, this activity strengthens collaboration between academics and the community as a crucial foundation for building business independence and sustainability. Thus, this community service program makes a tangible contribution to rural economic empowerment based on local potential.